STRUCTURE AND INFLUENCE OF THE MEDIA FIELD ("Conference on Universal Science Research 2023", 2023)
This article presents the facts that the global changes taking place in the environment surrounding print media have a significant impact on their character and changes in the economic, political, and technological layers of society.